„Wielka” i „Mała Rodzina Marii” w ikonografii chrześcijańskiej. Krótka historia tematu i jego realizacje na terenie Wielkopolski - Wajroch, Agnieszka (Ecclesia. Studia z Dziejów Wielkopolski, 2015)
The article deals with the iconography of the theme of the “great” and “small” family of Mary in Greater Poland. Most of the representations are not evidenced in the Bible. The author reviews the literature of the subject and presents examples of the realization of this theme in Greater Poland: Prochy, Tarnowo Połuckie, Skarbaszewo. Representations of this and related content were popular in medieval piety, especially in middle-class circles. In Greater Poland sculpted representations of the “small” Family of Mary enjoyed larger popularity than painted ones.